Evaluation of the eco-compatibility of polyamidoamines by means of seed germination test. (March 2022) - Alongi, Jenny; Costantini, Alberto; Ferruti, Paolo; Ranucci, Elisabetta
Highlights: The eco-compatibility of water soluble polyamidoamines has never been tested. The glycine-derived polyamidoamine M-GLY was subjected to seed germination test. Freshly prepared and aged M-GLY aqueous solutions proved eco-compatible. The eco-compatibility of M-GLY well compared with that of dextran. M-GLY oligomers with high amounts of reactive terminals were also not eco-toxic. Abstract: The eco-compatibility of the glycine-derived polyamidoamine M-GLY, chosen as the benchmark for water-soluble polyamidoamines, was investigated by means of the seed germination test using watercress seeds. The percent germinated seeds and their root elongation were measured, and the corresponding germination index (GI) calculated for each set of data obtained by incubating the seeds with M-GLY aqueous solutions with concentration in the range 0.156 – 5.0 mg mL −1 . The results obtained with M-GLY were compared with those obtained with 0.1% potassium dichromate and distilled water, as positive and negative blanks, and aqueous solutions of dextran, chosen as reference biocompatible polymer, having the same concentrations of M-GLY. M-GLY solutions with concentrations 5.0 and 2.5 mg mL −1 aged 98 days in water and, finally, α, ω-glycine- and α, ω-acrylamide-end-terminated M-GLY oligomers with different chain length were also tested. None of the M-GLY and aged M-GLY solutions inhibited germination and root elongation of watercress seeds as revealed by the GI values invariably higher than 1. In some cases, GI >> 1, suggesting a fertilizing effect. As for the differently end-functionalized M-GLY oligomers, they inhibited the root elongation at the maximum concentration tested, i.e. 5.0 mg mL −1 . In most conditions the M-GLY oligomers exhibited GI ≥ 1 and in some instances GI ≥ 1.2, suggesting a fertilizing effect.